The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Ionic desorption in valence- and core- excited polymers: poly(vinyl chloride) and poly(vinylidene chloride)

Abstract: Photon stimulated ion desorption (PSID) studies have been performed in poly(vinyl chloride) (PVC) and poly(vinylidene chloride) (PVDC) using synchrotron radiation, covering from valence to core electron (Cl 2p and C 1s) energy ranges. Data acquisition was performed at the TGM beam line from the Brazilian Synchrotron Light Source (LNLS), operating in a multi-bunch mode and using a time-of-flight mass spectrometer (TOF-MS). A new pulsed system developed uses as a trigger for the TOF-MS experiments the pulsed ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In particular, our previous photon stimulated ion desorption (PSID) studies performed on PVC and PVDC films with photon energies covering the valence, Cl 2p and C 1s energy ranges showed element-selectivity as evidenced by an increase in the chlorine ion yield around the Cl 2p-edge as compared to the other excitation energies. This feature was associated to a resonant Auger process along the Cl 2p-edge [9,10]. Similar ion desorption results were obtained for PVDC [10].…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…In particular, our previous photon stimulated ion desorption (PSID) studies performed on PVC and PVDC films with photon energies covering the valence, Cl 2p and C 1s energy ranges showed element-selectivity as evidenced by an increase in the chlorine ion yield around the Cl 2p-edge as compared to the other excitation energies. This feature was associated to a resonant Auger process along the Cl 2p-edge [9,10]. Similar ion desorption results were obtained for PVDC [10].…”
Section: Introductionsupporting
confidence: 83%
“…This feature was associated to a resonant Auger process along the Cl 2p-edge [9,10]. Similar ion desorption results were obtained for PVDC [10]. Positive and negative electron stimulated ion desorption (ESID) performed on PVC films as a function of the electron energy indicated that at higher electron energies, inner-shell ionization processes followed by Auger decay play an important role in the positive ion desorption of chlorine species.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations